Development of adaptive qualities of students in the course of boxing classes - Aleksey D. Sheyder (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper considers the development of the student’s adaptive qualities by means of boxing with elements of problem-situational learning as qualities that positively affect adaptation to a new social space. The aim of this study is to experimentally check the influence of physical education by means of boxing with elements of problem-situational learning on the development of adaptive qualities of students in the educational space of a higher educational institution. An assessment of the emerging alarming situation was carried out with the help of a questionnaire specially adapted for this purpose «Hospital Anxiety and Depression Scale (HADS)» and «Psychical Stress Scales» (PSM-25) of Lemours – Tiesier – Phillon. The survey was conducted among students of Samara State Technical University (SamSTU), the first group of which attended elective boxing classes and the second group of students attended standard physical education classes. In the course of the study, the concept of adaptive qualities of a student was clarified, as well as the influence of physical education by means of boxing on the development of adaptive qualities of students in the educational environment of the university was established. Namely, an empirical study conducted among students of SamSTU showed that students attending elective boxing classes with elements of problem-situational training are more adapted to stressful situations, what plays an important role in the development of a future engineer personality.